Computer and Information Sciences Proceedings of the 25th International Symposium on Computer and Information Sciences - Gelenbe, Erol.; Lent, Ricardo; Sakellari, Georgia; Sacan, Ahmet; Toroslu, Hakki; Yazici, Adnan; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Computer and Information Sciences is a unique and comprehensive review of advanced technology and research in the field of Information Technology. It provides an up to date snapshot of research in Europe and the Far East (Hong Kong, Japan and China) in the most active areas of information technology, including Computer Vision, Data Engineering, Web Engineering, Internet Technologies, Bio-Informatics and System Performance Evaluation Methodologies.
Algorithms -- Modeling and Performance Evaluation of Systems and Networks -- Bioinformatics & Bioengineering -- Data Engineering -- Learning and Clustering Methods -- Computer and Wireless Networks -- Computer Vision and Image Processing -- Web Systems -- Discovery Science -- Distributed and Parallel Algorithms -- Hardware Design.
Keywords: Computer science; Computer vision; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics